Job insecurity, emotional exhaustion, and workplace deviance: The role of corporate social responsibility - Jia, Xingping; Liao, Shudi; Yin, Wenjun (Frontiers in Public Health, 2022)
Job insecurity is one of top concerns in the contemporary workplace, which significantly affects emotional exhaustion and workplace deviance. Thus, this study seeks to explore the buffering role of employees’ corporate social responsibility (CSR) perceptions to against the effect of job insecurity. Based on micro-CSR literature and social identity theory, this study tested the proposition that employees’ CSR perceptions moderate the relationship between job insecurity and emotional exhaustion through organizational identification. Using three-wave data collected from 145 employees in one of China’s biggest computer equipment providers, we found that employees’ CSR perceptions alleviate (exacerbate) the negative relationship between quantitative (qualitative) job insecurity and emotional exhaustion via organization identification. Our findings provided new insights to scholars and managers in dealing with job insecurity.